Text Messaging in English and Arabic with Reference to Translation - Ahmed Adel Nouri; Omar Ali Hussein (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
In the twenty-first century, many people now live their lives through text messaging. In fact, you can witness people using their cell phones to send character-based messages to their friends, classmates, family members, and coworkers in malls, schools, and pretty much anywhere else. The popularity of this method of communication has increased particularly among young people. One benefit is that technology enables people to speak with others virtually anywhere. Second, it enables individuals to speak softly, which is useful in noisy places like bars, where it would be challenging to have a productive conversation over the phone, or when extraneous communication needs to be done quietly, such as in a school. Thirdly, it combines some of the advantages of phone and email communication by allowing them to communicate both synchronously (i.e., two-way communication occurs concurrently) and asynchronously (i.e., two-way communication is delayed). The usage of acronyms, abbreviations, and other shorthand notations has become commonplace in this technology's creation of a new language form. The focus of this research is on these qualities specifically and how they are used. The aim of this study was to analyze not only how frequently but also how these symbolic expressions are used in relation to the linguistic functions that they signal, which was followed by a number of discoveries.